A Mechanistic Model for Naive CD4 T Cell Homeostasis in Healthy Adults and Children - Hapuarachchi, Tharindi; Lewis, Joanna; Callard, Robin (Frontiers in Immunology, 2013)
The size and composition of the T lymphocyte compartment is subject to strict homeostatic regulation and is remarkably stable throughout life in spite of variable dynamics in cell production and death during T cell development and immune responses. Homeostasis is achieved by careful orchestration of lymphocyte survival and cell division. New T cells are generated from the thymus and the number of peripheral T cells is regulated by controlling survival and proliferation. How these processes combine is however very complex. Thymic output increases in the first year of life and then decreases but is crucial for establishing repertoire diversity. Proliferation of new naive T-cells plays a crucial role for maintaining numbers but at a potential cost to TCR repertoire diversity. A mechanistic two compartment model of T-cell homeostasis is described here that includes specific terms for thymic output, cell proliferation and cell death of both resting and dividing cells. The model successfully predicts the homeostatic set point for T-cells in adults and identifies variables that determine the total number of T cells. It also accurately predicts T cell numbers in children in early life despite rapid changes in thymic output and growth over this period.